2021
DOI: 10.1002/gj.4100
|View full text |Cite
|
Sign up to set email alerts
|

Petrogenesis and tectonic setting of Mid‐Triassic volcanic rocks in the East Kunlun orogenic belt, NW China: Insights from geochemistry, zircon U–Pb dating, and Hf isotopes

Abstract: The Elashan magmatic belt is located at the eastern margin of the East Kunlun orogenic belt (E‐KOB) in northwestern China, where voluminous magmatism occurred during the Late Permian to Late Triassic. Mid‐Triassic volcanism produced the Xilikete Formation, which shows a geochemistry similar to that of highly fractionated I‐type (HFI) volcanic rocks. These rocks are characterized by high SiO2 (73.82–74.97 wt%), differentiation index (DI; 91.01–94.69), and alkalis (e.g., high K2O + Na2O, with K2O/Na2O ratios gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 88 publications
(107 reference statements)
0
10
0
Order By: Relevance
“…Among them, the granodiorite often contains MMEs, and the volcanic rocks are mostly rhyolite, dacite, andesite, and pyroclastic rocks of the same period. The zircon Hf isotope results showed that the magma was mainly derived from the partial melting of the lower crust of the Mesoproterozoic, and some of them mixed with a small amount of mantle material [2,3,5,6]. In terms of sedimentary assemblages, the Middle Triassic Xilikete Formation has the characteristics of marine-continental sedimentary assemblages [73] and an angular unconformity contact with the Late Triassic continental volcanic rocks (Elashan Formation and Babaoshan Formation, Figure 13), indicating that the East Kunlun Orogenic Belt was in a rapid uplift stage during the Middle Triassic, representing the collision between the BayanHar Block and the Eastern Kunlun Block and the disappearance of the Paleo-Tethys Ocean, resulting in local deposition.…”
Section: Tectonic Implicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among them, the granodiorite often contains MMEs, and the volcanic rocks are mostly rhyolite, dacite, andesite, and pyroclastic rocks of the same period. The zircon Hf isotope results showed that the magma was mainly derived from the partial melting of the lower crust of the Mesoproterozoic, and some of them mixed with a small amount of mantle material [2,3,5,6]. In terms of sedimentary assemblages, the Middle Triassic Xilikete Formation has the characteristics of marine-continental sedimentary assemblages [73] and an angular unconformity contact with the Late Triassic continental volcanic rocks (Elashan Formation and Babaoshan Formation, Figure 13), indicating that the East Kunlun Orogenic Belt was in a rapid uplift stage during the Middle Triassic, representing the collision between the BayanHar Block and the Eastern Kunlun Block and the disappearance of the Paleo-Tethys Ocean, resulting in local deposition.…”
Section: Tectonic Implicationsmentioning
confidence: 99%
“…The East Kunlun Orogenic Belt is a typical multi-cycle complex orogenic belt that retains information related to the evolution of the Proto-Teyhys Ocean and the Paleo-Tethys Ocean, and records the information and dynamic process of the formation and evolution of the northern Qinghai-Tibet Plateau. Among them, with the exposure of voluminous magmatic rocks related to the northward subduction of the Paleo-Tethys Ocean in the Late Paleozoic-Early Mesozoic as the main feature, many scholars have carried out relevant research on this area [1][2][3][4][5][6]. However, there has been controversy over the origin, petrogenesis, tectonic background, and deep process of the huge granitic magma in the late Permian-Triassic period in the East Kunlun Orogenic Belt at present.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The EKOB in the Qinghai‐Tibetan Plateau is considered to undergo multi‐stages of tectonic‐magmatic evolution (Y. X. Chen, Pei, Li, Li, Liu, & Wang, 2017; Y. P. Dong et al, 2018; Du et al, 2017; J. J. Kong, Niu, He, Zhang, & Shao, 2020; Z. C. Li, Pei, et al, 2017; Y. G. Liu et al, 2018, 2019; X. Xu et al, 2020; Z. W. Zhang et al, 2018; M. J. Zhang et al, 2021). The evolutionary history of the Palaeo‐Tethys within the EKOB has attracted considerable attention over the past decades (Y. P. Dong et al, 2018; Gao & Sun, 2021; Hu et al, 2016; Huang et al, 2014; J. J. Kong et al, 2020; H. L. Kong et al, 2021; Y. Y. Liang, Xia, Ma, Zhao, & Guo, 2020; Richards, 2015; Shao et al, 2017; Song et al, 2020; Tian et al, 2021; J. Y. Zhang, Ma, Xiong, & Liu, 2012; Zhao et al, 2019). However, the precise timing of the termination of the continental collision and the beginning of the post‐collision of Palaeo‐Tethys along the EKOB remains poorly constrained.…”
Section: Introductionmentioning
confidence: 99%
“…L. Kong et al, 2021;Y. Y. Liang, Xia, Ma, Zhao, & Guo, 2020;Richards, 2015;Shao et al, 2017;Song et al, 2020;Tian et al, 2021;Zhao et al, 2019).…”
mentioning
confidence: 99%